2021
DOI: 10.1016/j.parkreldis.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurofilament light in Huntington's disease: A marker for disease onset, but not symptom progression

Abstract: To investigate whether plasma NfL levels correlate with clinical symptom severity in premanifest (PM) and manifest HD (HD) individuals, and whether a NfL cut-point could distinguish PM from HD patients with reasonable accuracy. Method: 98 participants (33 control, 26 PM, 39 HD), underwent blood sample collection and clinical assessment, using both UHDRS and non-UHDRS measures, at one academic HD Center. Years to onset (YTO), probability of disease onset in 5 years, and predicted years until 60% onset probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 29 publications
9
23
0
Order By: Relevance
“…Although early mHtt lowering delayed an increase of NFL in the CSF, neither early nor late moderate global mHtt-lowering could prevent or reverse the increase of NFL in the CSF when measured at 12 months of age. This is consistent with CSF NFL correlating with disease onset, but not tracking with disease progression (39).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although early mHtt lowering delayed an increase of NFL in the CSF, neither early nor late moderate global mHtt-lowering could prevent or reverse the increase of NFL in the CSF when measured at 12 months of age. This is consistent with CSF NFL correlating with disease onset, but not tracking with disease progression (39).…”
Section: Discussionsupporting
confidence: 77%
“…In HD patients, an increase in neurofilament light chain (NFL) levels in the plasma and CSF have been reported to correlate with the onset of clinical symptoms and to increase during disease progression (36)(37)(38)(39)(40). Previously, NFL was reported to increase in the CSF of the R6/2 mouse model (41), therefore, we examined NFL levels in the CSF from mice with and without mHtt lowering.…”
Section: Early Mhtt Lowering Delays Elevation Of a Neurodegeneration ...mentioning
confidence: 98%
“…Our results correspond with work in spinocerebellar ataxia showing that NF-L was stable during the study period, despite clinical progression ( 14 ). A study in individuals with HD likewise demonstrated that NF-L was not associated with clinical outcomes in individuals with manifest disease ( 13 ). Adult-onset DM1 is characterized by slow clinical disease progression ( 30 ), indicating that longer follow-up periods may be required to detect changes in blood-based markers.…”
Section: Discussionmentioning
confidence: 99%
“…While NF-L has been studied extensively in individuals with neurodegenerative illness (12)(13)(14)(15)27); its utility as biomarker of CNS pathology in DM1 had not been determined prior to this study. Plasma NF-L was elevated among individuals with manifest DM1 relative to controls, and those with PreDM1 exhibited intermediate levels compared with controls and manifest DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation